Understanding bending-induced loss and bending-enhanced higher-order mode suppression in negative curvature fibers - Wang, Yuxi (2022)
We present a numerical analysis on bending-induced loss and bending-enhanced higher-order mode suppression in negative curvature fibers. We provide underlying mechanisms on how geometrical parameters affect the bending properties. We find that fiber parameters influence the bending performance by altering the resonant coupling conditions, as well as light leakage through inter-tube gaps. We identify regions in the parameter space that exhibit excellent bending properties and offer general guidelines for designing negative curvature fibers that are less sensitive to bending. Moreover, we explore the possibility of enhancing higher-order core mode suppression through mechanical bending. We find that up to nine-fold increase in the higher-order mode extinction ratio can be achieved by bending the fiber.